Further notes on the taxonomy of four species of Physalaemus (Anura, Leiuperidae) from the Atlantic Forest of Southeastern Brazil - Giaretta, Ariovaldo A.; Martins, Lucas B.; Santos, Marcela P. Dos (Zootaxa, 2009)
We analyzed the advertisement calls of four species of Physalaemus (P. olfersii, P. moreirae, P. bokermanni, and P. jordanensis) from the Brazilian Atlantic Forest. The tadpole of P. olfersii is described for the first time. Calls of all species are composed by just one kind of note. Those of P. olfersii are long (4035 ms), pseudo-pulsed, with dominant frequency around 2375 Hz; 7–10 sidebands are well distinguishable. The calls of P. moreirae are pulsed, with duration about 604 ms, mean dominant frequency around 1369 Hz and 3–5 sidebands. Physalaemus bokermanni has a call structurally different from the other species by the absence of sidebands or harmonics, larger inter-pulse breaks (around 34–42 ms) and a wider frequency range (around 3700 Hz). Calls of P. jordanensis are pulsed and have 7–8 harmonics, last about 1068 ms and dominant frequency around 2742 Hz. Physalaemus olfersii tadpoles show typical features of other Physalaemus larvae, measuring about 19 mm in total length. Our data on call of P. olfersii suggest that a broader taxonomic survey would be worthwhile by revealing that different species are included under this name. Calls of P. moreirae and P. bokermanni, in general, are in agreement with those previously described from other sites, but complementary features are given. Those of Physalaemus jordanensis show some differences in relation to the calls from the type locality, but additional data are still necessary for a taxonomic conclusion.